Profiling Antibiotic Susceptibility among Distinct Enterococcus faecalis Isolates from Dental Root Canals - Daniel Manoil; Ender Efe Cerit; Hong Fang; Stéphane Durual; Malin Brundin; Georgios N. Belibasakis (MDPI AG, 2023)
Enterococcus faecalis, a leading multi-resistant nosocomial pathogen, is also the most frequently retrieved species from persistently infected dental root canals, suggesting that the oral cavity is a possible reservoir for resistant strains. However, antimicrobial susceptibility testing (AST) for oral enterococci remains scarce. Here, we examined the AST profiles of 37 E. faecalis strains, including thirty-four endodontic isolates, two vanA-type vancomycin-resistant isolates, and the reference strain ATCC-29212. Using Etest gradient strips and established EUCAST standards, we determined minimum inhibitory concentrations (MICs) for amoxicillin, vancomycin, clindamycin, tigecycline, linezolid, and daptomycin. Results revealed that most endodontic isolates were susceptible to amoxicillin and vancomycin, with varying levels of intrinsic resistance to clindamycin. Isolates exceeding the clindamycin MIC of the ATCC-29212 strain were further tested against last-resort antibiotics, with 7/27 exhibiting MICs matching the susceptibility breakpoint for tigecycline, and 1/27 reaching that of linezolid. Both vanA isolates confirmed vancomycin resistance and demonstrated resistance to tigecycline. In conclusion, while most endodontic isolates remained susceptible to first-line antibiotics, several displayed marked intrinsic clindamycin resistance, and MICs matched tigecycline's breakpoint. The discovery of tigecycline resistance in vanA isolates highlights the propensity of clinical clone clusters to acquire multidrug resistance. Our results emphasize the importance of implementing AST strategies in dental practices for continued resistance surveillance.